Integration of Islamic values based mindfulness as an effort to improve the psychological well being of students in Islamic boarding schools: A conceptual study - Ulil Abshar; Putri, Citra Pangestika (Arshaka: Social Sciences and Education, 2025)
Students in pesantren face academic and social pressures that have an impact on their psychological well-being and study concentration. This article aims to comprehensively examine the effectiveness  of the integration of mindfulness based on Islamic values in improving the psychological well-being and learning concentration of students. This study uses a qualitative approach with a literature study method. The results of the study show that the combination of the principles  of mindfulness with Islamic values such as patience, gratitude, sincerity, tawakal, and tazkiyatun nafs can be a holistic and contextual intervention approach. This integration has the potential to support the development of culturally relevant student coaching methods, improve emotional regulation and focus on learning, and effectively improve the spiritual and psychological well-being of students.